Glycerol steam reforming over La–Ce–Co mixed oxide-derived cobalt catalysts. Issue 56 (19th June 2015) - Surendar, M.; Sagar, T. V.; Babu, B. Hari; Lingaiah, N.; Rao, K. S. Rama; Prasad, P. S. Sai
<x xml:space="preserve">Abstract</x> Cobalt nano particles derived from the La–Ce–Co mixed oxide, after reduction, are highly active for glycerol steam reforming to produce hydrogen.